Microflow LC-MS Bottom-Up Proteomics Using 1.5 mm Internal Diameter Columns - Jadeja, Siddharth; Naplekov, Denis K; Starovoit, Mykyta R; Plachká, Kateřina; Ritchie, Harald; Lawhorn, Jason; Sklenářová, Hana; Lenčo, Juraj (ACS omega, 2025)
Microbore columns with a 1.0 mm inner diameter (i.d.) have gained popularity in microflow liquid chromatography-mass spectrometry (LC-MS) workflows for exploratory proteomics applications due to their high throughput, robustness, and reproducibility. However, obtaining highly efficient separation using these columns remains unachievable, primarily due to significant radial flow heterogeneity caused by uneven particle packing density across the column cross-section. In this study, we evaluated the integration of a 1.5 mm i.d. column, which offers greater packing uniformity and reduced radial flow dispersion, into a microflow LC-MS setup for bottom-up proteomics analysis. The performance of the 1.5 mm i.d. column was compared with that of the 1.0 mm i.d. column using protein samples of varying complexity. The results demonstrate that 1.5 mm i.d. columns provide superior chromatographic separation and better compatibility with conventional-flow LC systems, yielding higher reproducibility and comparable protein and peptide identifications to the 1.0 mm i.d. columns at higher sample amounts. These findings suggest that 1.5 mm i.d. columns could be a suitable alternative to 1.0 mm i.d. columns for microflow LC-MS/MS proteomic analysis, particularly in laboratories with only conventional-flow LC systems.